Pengaruh Kualitas Pelayanan Terhadap Kepuasan Konsumen Perusahaan Daerah Air Minum (Pdam) Di Makassar - Rusdi, Rusdi; Parawangi, Anwar; Malik, Ihyani (Universitas Muhammadiyah Makassar, 2021)
This study purposed to find out how the quality of service of regional water supply companies (PDAM) in Makassar City, customer satisfaction, and the influence of service quality on customer satisfaction of regional water supply companies (PDAM) in Makassar city. This study used quantitative descriptive research, while the data collection techniques used observation, questionnaires and documentation. The total population of PDAM consumers in Makassar city was 172,000. Data Sources used primary data and secondary data, data analysis techniques were data reduction, data presentation and verification. The results showed that the service quality of PDAM at Makassar City based on what consumers expected was considered very important. This was proved by the overall average score of 4.25 respondents 'statements at intervals of 4.20 to 5.00, then the consumer satisfaction of PDAM at Makassar City based on respondents' statements was very good. This could be seen from the average value of customer satisfaction amounting to 4.21 at intervals of 3.40-4.19, and based on the results of the influence of service quality of PDAM at Makassar City on customer satisfaction that there was an influence of service quality (X) on satisfaction consumer (Y). while the value of t-count was 4.002.Pengaruh Kualitas Pelayanan Terhadap Kepuasan Konsumen Perusahaan Daerah Air Minum (Pdam) Di Makassar